Id2 Represses Aldosterone-Stimulated Cardiac T-Type Calcium Channels Expression - Ito, Jumpei (Int J Mol Sci, 2021)
Aldosterone excess is a cardiovascular risk factor. Aldosterone can directly stimulate an electrical remodeling of cardiomyocytes leading to cardiac arrhythmia and hypertrophy. L-type and T-type voltage-gated calcium (Ca(2+)) channels expression are increased by aldosterone in cardiomyocytes. To further understand the regulation of these channels expression, we studied the role of a transcriptional repressor, the inhibitor of differentiation/DNA binding protein 2 (Id2). We found that aldosterone inhibited the expression of Id2 in neonatal rat cardiomyocytes and in the heart of adult mice. When Id2 was overexpressed in cardiomyocytes, we observed a reduction in the spontaneous action potentials rate and an arrest in aldosterone-stimulated rate increase. Accordingly, Id2 siRNA knockdown increased this rate. We also observed that CaV1.2 (L-type Ca(2+) channel) or CaV3.1, and CaV3.2 (T-type Ca(2+) channels) mRNA expression levels and Ca(2+) currents were affected by Id2 presence. These observations were further corroborated in a heart specific Id2- transgenic mice. Taken together, our results suggest that Id2 functions as a transcriptional repressor for L- and T-type Ca(2+) channels, particularly CaV3.1, in cardiomyocytes and its expression is controlled by aldosterone. We propose that Id2 might contributes to a protective mechanism in cardiomyocytes preventing the presence of channels associated with a pathological state.